PENERAPAN STRATEGI PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD INPRES ANTANG I KECAMATAN MANGGALA KOTA MAKASSAR - Nur Fadillah; Nurlina; Hilmi Hambali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this study was that teachers' suboptimal use and implementation of learning strategies led to a learning environment that left students feeling bored and tired during the lesson, resulting in below-average science learning outcomes. This study aimed to assess the effectiveness of implementing the Scramble learning strategy in improving science learning outcomes in fourth-grade students. The method used was an experimental one-group pretest-posttest. The sample consisted of 33 fourth-grade students at SD Inpres Antang I. Data collection techniques included observation, testing, and documentation. The results showed that the learning process using the Scramble learning strategy had an impact on students' science learning outcomes, as evidenced by the increase in pretest and posttest scores. In the experimental class studied, the average posttest was higher than the pretest. The average posttest was 83.03, while the average pretest was 37.57. Therefore, it can be concluded that the Scramble learning strategy significantly influences students' science learning outcomes.